Development of a Popular Scientific Book about Sungkai Population Structure (Peronema canescens Jack.) - Anggraini, Heni Wahyu; Dharmono, Dharmono; Irianti, Riya (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2024)
Science always follows changing times that have an impact on everyday life, including in the field of education. Therefore, education must be carried out effectively in order to create quality education and improve the quality of human resources. A quality education process requires the support of learning media. Based on the results of observations in the Plant Ecology course, the use of learning media is still lacking so students find it difficult to understand material about population structure. Popular Scientific Books (PSB) are a form of learning media that can be developed to solve existing problems. This research aims to determine the feasibility of a PSB regarding the population structure of Sungkai (Peronema canescens Jack.) in the Danau Sari Embun area, Tanah Laut Regency. The method used is the research and development method of the 5 phase PLOM model. The results of this research are based on the validity test of learning media which is in the very valid category and in the readability test the students received very good criteria. So it can be concluded that the learning media Popular Scientific Books can be used as a learning media.